2015
DOI: 10.1111/jav.00652
|View full text |Cite
|
Sign up to set email alerts
|

First archaeogenetic results verify the mid‐Holocene occurrence of Dalmatian pelican Pelecanus crispus far out of present range

Abstract: Th e paper presents an evaluation of subfossil bird bones from archaeological and geological sites in Europe that shows that birds of the genus Pelecanus occurred far out of their present range between 7.4 and 5.0 ka BP in the Danish archipelago. Additionally, from other northwestern European regions mid-Holocene records of pelicans are known. However, due to morphological similarities there are diffi culties in species identifi cation. In this paper ancient DNA barcoding techniques were used to clarify the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 42 publications
0
19
0
2
Order By: Relevance
“…Thereby, the study gives evidence for the presence of a typical bird species for the eastern Mediterranean and Black Sea area far to the north. We demonstrated that between 7,400 and 5,000 years ago, the number of Dalmatian pelican records in the west Baltic Sea area is so numerous that they probably do not originate from vagrants, but point to a regular expansion of the species range (Nikulina, Schmölcke 2015b). Very probably, these changes in distribution ranges were caused by the warm climate during the mid-Holocene Atlantic period.…”
Section: Baltica 23mentioning
confidence: 75%
See 3 more Smart Citations
“…Thereby, the study gives evidence for the presence of a typical bird species for the eastern Mediterranean and Black Sea area far to the north. We demonstrated that between 7,400 and 5,000 years ago, the number of Dalmatian pelican records in the west Baltic Sea area is so numerous that they probably do not originate from vagrants, but point to a regular expansion of the species range (Nikulina, Schmölcke 2015b). Very probably, these changes in distribution ranges were caused by the warm climate during the mid-Holocene Atlantic period.…”
Section: Baltica 23mentioning
confidence: 75%
“…Ancient DNA can also help to distinguish between closely related animal species with nearly identical morphological bone characteristics. This has been demonstrated in fish species (Nikulina, Schmöl-cke 2015a) and in birds (Nikulina, Schmölcke 2015b). In both cases, it was the ancient DNA analysis that finally allowed the reconstruction of the former distribution of the investigated species.…”
Section: O N C L U S I O N Smentioning
confidence: 88%
See 2 more Smart Citations
“…Breitengrades verbreitet ist, während des HKO auch Norddeutschland und Dänemark besiedelt hat [13]. Fast exotisch mag die durch zahlreiche Knochenfunde in archäologischen Siedlungen nachgewiesene Präsenz des Krauskopfpelikans ( Pelecanus crispus ) im südwestlichen Ostseegebiet klingen [14]. Auch der Wels ( Silurus glanis ) weist im HKO eine weiter nördliche bzw.…”
Section: Paläoklima Und Biodiversitätunclassified